A DIFFERENCES IN NURSES' KNOWLEDGE ABOUT PATIENT SAFETY BEFORE AND AFTER RECEIVING EDUCATION ON PREVENTING PHLEBITIS INCIDENTS IN DD INTEGRATED HEALTH HOUSE HOSPITAL IN 2023 - Eneng Hasanah; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Patient safety in terms of phlebitis has become a significant concern, as the incidence of phlebitis is reported to increase every year. Nurses, as key players in healthcare facilities, must have good knowledge of patient safety. This research aims to determine the difference in nurses' knowledge of patient safety before and after receiving education on phlebitis prevention in preventing phlebitis incidents at RST DD Hospital. This study used a quasi-experimental design with a pretest-posttest with control group design. The population included all nurses, and the sample was taken considering the highest incidence of phlebitis in the inpatient ward, resulting in 77 respondents. Data analysis was conducted using the Dependent T-test (SPSS Mann Whitney). The respondents' knowledge before education was 17,00 and after education, it was 47,57 the positive difference between before and after education was 33, indicating that 33 respondents experienced an increase in knowledge after education. This was proven by the statistical test results comparing the pretest and posttest scores in the intervention group using the Mann-Whitney test, which yielded a p-value of 0.000; α = 0.05 with a 95% confidence level. There is a difference in nurses' knowledge of patient safety after receiving education. Efforts are needed to improve nurses' knowledge through various activities such as seminars, case rounds, training, etc.